2019
DOI: 10.18632/aging.101770
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyperglycemia regulates microglia polarization through ERK5

Abstract: Diabetic patients are prone to developing Alzheimer’s disease (AD), in which microglia play a critical role. However, the direct effect of high glucose (HG) on microglia and the role of extracellular-signal-regulated kinase 5 (ERK5) signaling in this interaction have not been examined before. Here, these questions were addressed in microglia cultured in HG versus normal glucose (NG) conditions. Initially, HG induced microglial differentiation into the M2a phenotype with concomitant ERK5 activation. However, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Inflammation plays a central role in the onset and progression of diabetic retinopathy ( Tang and Kern, 2011 ; Semeraro et al, 2015 ). Much of the innate immune receptor signaling that elicits inflammation flows through the ERK5 signaling cascade ( Wang and Tournier, 2006 ; Stecca and Rovida, 2019 ), which is increased in Type II diabetics ( Chen et al, 2019 ), and our data suggest in the retina of STZ-diabetic mice. Additionally, ERK5 can induce and enhance the production of multiple growths factors; including VEGF ( Stecca and Rovida, 2019 ).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Inflammation plays a central role in the onset and progression of diabetic retinopathy ( Tang and Kern, 2011 ; Semeraro et al, 2015 ). Much of the innate immune receptor signaling that elicits inflammation flows through the ERK5 signaling cascade ( Wang and Tournier, 2006 ; Stecca and Rovida, 2019 ), which is increased in Type II diabetics ( Chen et al, 2019 ), and our data suggest in the retina of STZ-diabetic mice. Additionally, ERK5 can induce and enhance the production of multiple growths factors; including VEGF ( Stecca and Rovida, 2019 ).…”
Section: Discussionsupporting
confidence: 57%
“…The cause of diabetic retinopathy is multifactorial, and an optimal therapeutic would halt multiple inflammatory processes, decrease VEGF production, cease neural cell dysfunction, and ablate vascular impairment. Extracellular signal-related kinase 5 (ERK5) is a mitogen-activated protein kinase (MAPK) that elicits the production of multiple inflammatory cytokines and enhances VEGF production in many inflammatory disorders and in diabetes ( Kondoh et al, 2006 ; Wang and Tournier, 2006 ; Hayashi et al, 2004 ; Dorado et al, 2008 ; Chen et al, 2019 ). ERK5 is the terminal member of a MAPK signaling pathway that can induce inflammation through a series of phosphorylation cascades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support this assumption, in vitro studies have provided evidence for glucose regulation of microglial activity. An elevated glucose concentration induces a morphological change from resting ramified microglia to activated ameboid microglia and stimulates expression and release of pro-inflammatory cytokines by primary microglia, BV-2 cells, and HMC3 cells [ 16 , 17 , 18 , 19 , 20 , 33 , 34 ]. The present study demonstrated that both the primary mouse microglia and SIM-A9 cells responded to increased concentrations of glucose as represented by increased expressions of c-Fos and pERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive activation may lead to the release of inflammatory cytokines, chemokines, reactive oxygen species, and nitric oxide, which can lead to neuronal dysfunction and death [ 80 , 81 , 82 , 83 ]. Exposure to chronic hyperglycemia has been associated with activation of microglia [ 84 ]. Furthermore, when studying the mouse microglial BV-2 cell line, exposure to glucose fluctuations resulted in increased markers of metabolic stress leading to apoptosis and/or autophagy [ 85 ] as well as leading to shifts in microglial polarization to the inflammatory M1 phenotype [ 53 ].…”
Section: Impact Of Gv On Central Nervous System Inflammationmentioning
confidence: 99%